ANALYSIS OF HIGH DOSE AND LONG-TERM PREDNISONE THERAPY ON OSTEOCALCIN LEVELS IN CHILDREN WITH NEPHROTIC SYNDROME (STUDY AT PEDIATRIC DEPARTMENT NEPHROLOGY DIVISION OF DR. SOETOMO TEACHING HOSPITAL SURABAYA) - Permatasari, Febrina Pritayuni; Asmaningsih, Ninik; Qibtiyah, Mariyatul; Yulistiani, Yulistiani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study to analyze osteocalcin levels in induction and alternate phase, associated with clinical manifestation. Methods: We conducted a prospective longitudinal study. This study was subject to approval by the Ethics Committee of Dr. Soetomo Teaching Hospital Surabaya. Osteocalcin levels were measured before and after induction phases and 4 weeks after the alternate phase. Samples were collected in the morning at 08.00-09.00 am. Results: A total of 15 patients were included in this study. The suppression of osteocalcin levels in the induction phase was 53.33%. After the alternate phase, osteocalcin levels increased 175.82%. Clinical manifestation as bone pain/cramps only appeared 33% in the induction phase and 20% in the alternate phase. The mean suppression of osteocalcin levels in the group with induction phase duration therapy â‰¥28 days and without calcium supplementation was higher than 21-27 days and with calcium supplementation. Osteocalcin levels increased in the alternate phase also in patients with and without calcium supplementation. The result of analysis showed there was no significant difference among all groups (p>0.05). Conclusion: Suppression of osteocalcin levels was reversible after the alternate phase. It shows that tapering off regimen is important. Clinical sign as pain bone/cramps almost showed no manifest in all of these patients. Â